Stigma, Securitization, and Military Authority: a Legal and Socio-Political Examination of Internal Conflicts - Arief Fahmi Lubis (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Internal conflicts often generate complex interactions between security imperatives, legal frameworks, and social perceptions. In many cases, military involvement in domestic security operations is accompanied by processes of stigmatization, whereby certain groups are labeled as threats to national stability. This article examines the socio-legal dimensions of such stigmatization and analyzes how law functions both as a mechanism of legitimization and as a constraint on military power. Drawing upon theories of stigma, securitization, and sociological jurisprudence, the study explores how the construction of “internal enemies” reshapes legal norms, affects civil-military relations, and influences public legitimacy. Using a qualitative socio-legal approach, the article argues that while security narratives may justify extraordinary measures, unchecked stigmatization risks undermining rule of law, social cohesion, and democratic accountability. The study contributes to the broader discourse on the relationship between military authority, law, and society in contexts of internal conflict.